Low Prevalence of Clinically High-Risk Women and Pathological Thyroid Ultrasound among Pregnant Women Positive in Universal Screening for Thyroid Disorders - Jiskra, J.; Bartáková, J.; Holinka, Š.; Límanová, Z.; Springer, D.; Antošová, M.; Telička, Z.; Potluková, E. (Experimental and Clinical Endocrinology & Diabetes, 2011)
It is controversial whether screening program for thyroid disorders in pregnancy should be universal or targeted case-finding.To evaluate the relationship between history, laboratory parameters and thyroid ultrasound (TUS) in pregnant women positive in universal screening.The screening included investigation of serum TSH (thyroid stimulating hormone) and TPOAb (antithyroperoxidase antibodies) in 5 520 unselected pregnant women in the 9–11th gestational week. In 822 the screening was positive: abnormal TSH (> 3.67 or < 0.06 mIU/l) and/or positive TPOAb (> 143 kIU/l). 200 consecutive women with positive screening were included it the study.41 women (21%) had transient gestational hyperthyroidism (TGH) and 159 (79%) had a thyroid pathology: 10 (5%) overt hypothyroidism; 76 (38%) subclinical hypothyroidism, 7 (3.5%) overt hyperthyroidism and 66 (33%) euthyroid TPOAb positivity. After exclusion of TGH, only 74/159 (47%) women were classified as high-risk for thyroid disease according to their history. There were no significant clinical and laboratory differences between the high- vs. low-risk women, except for higher proportion of FT4<75th percentile (P=0.008) and larger thyroid volume in the high-risk group (P=0.04). Finally, only 66/126 (52%) of TPOAb-positive pregnant women had autoimmune pattern in TUS in comparison with 41/49 (84%) TPOAb-positive non-pregnant control women of comparable age (P<0.001).Less than half of the positively screened pregnant women can be classified as high-risk and almost half of them had not autoimmune pattern in TUS. High- and low-risk pregnant women have similar clinical and laboratory characteristics.
Keywords: screening; antibodies to thyroperoxidase; thyroid-stimulating hormone; pregnancy; thyroid ultrasound